Application Of Information Session Information System As Media Submission Of Final Results Comprehensive Session - Leonard, James; Damanik, Dian Maharani; Amrikhasanah, Oktika Gita (ADI Journal on Recent Innovation, 2019)
Good information that is based on data that has been processed properly so as to generate useful communication. The trial assessment system has 3 parts, but the system is not mutually integrated because 2 of them can already be accessed online while the examiner's assessment system still uses the local network. In the grading system, the examiner has a session news information system that is useful for conveying the final results of the session to the trial participants. This is because as technology advances are utilized as well as possible by educational institutions in this case namely universities to be used in a comprehensive session of thesis students or final assignments. Therefore, development is carried out on the examiner's assessment system so that it can be accessed online, where there is a trial news information system. The research was conducted using the method of observation, interviews and literature to maximize this research. The trial news information system is a very important system when a comprehensive trial process takes place. This is because the news information system of the hearing has information about the grades, grades and status obtained by the trial participants. This certainly becomes very vital in the trial assessment system. The display that will be developed in the examiner's rating system will be user friendly, making it easier for the board of examiners to use it. Even though the system was developed but did not change the original flow of the examiner's assessment system so that the board of examiners could adjust well to the new system, along with the news information system of the trial. With the existence of a hearing news information system, it makes the comprehensive trial process perfect and the trial assessment system becomes integrated again as before.